Revision of the genus Allometopon Kertész (Diptera: Clusiidae) - Lonsdale, Owen (Zootaxa, 2016)
The genus Allometopon Kertész is revised, recognizing 68 species, including 5 undescribed species known only from females. The genus is mostly known from the Australian (30 spp.) and Oriental Regions (33 spp.—only one unnamed female is found in both Australian and Oriental Regions), but also the Afrotropical (5 spp.) and Palaearctic Regions (1 sp.). Most Allometopon are new to science, with 40 new species described here: A. acum, A. asylum, A. atribatum, A. bharetum, A. bivittatum, A. cavernosium, A. cheiris, A. conopeum, A. eotoxon, A. fumihalteratum, A. fuscinum, A. gaimarii, A. giallo, A. glochis, A. gracile, A. hauseri, A. hesperotoxon, A. hirsutum, A. horridum, A. infernum, A. juxtum, A. kokodensis, A. lunatum, A. lux, A. macalpinei, A. machaeroges, A. magnum, A. monstrum, A. nyx, A. phenomena, A. philomela, A. platystylum, A. plicatum, A. procne, A. selenis, A. solare, A. suspirium, A. tenebrae, A. tetrathrix, and A. trilobellum. Calometopon Frey syn. nov. (subgenus of Allometopon with type species A. nobile Frey, by original designation) is included as a junior synonym of Allometopon. Sobarocephala geniculata Sasakawa is recombined as Allometopon geniculatum comb. nov. A key, illustrations and photographs are provided for species.